Psychological Factors that Affect the Interpersonal Conflict Between Mother and Son in Western Dramas (With Reference to Selected Dramas) - Kodagoda, Asanka (Faculty of Humanities, University of Kelaniya, 2023)
The conflict of a drama is based on its character. It happens as a result of a disagreement or an opposition. The conflict between two characters is identified as interpersonal conflict. This interpersonal conflict is popularly depicted in mother-son relationships in Western Dramas. It is evident that most of the plays written in Western literature are portrayed from a deep psychological angle. Many psychological concepts and theories have been composed in the recent past. Yet, it is evident that early dramatists were successful in effectively bringing out the emotions and feelings of humankind. For instance, Greek, Elizabethan, European, Russian, and modern American play scripts can be considered. Sigmund Freud explains the theory of psychoanalysis through four main concepts. Namely, Levels of Mind, Structures of Personality, Defense Mechanism and Psychosexual Development Stage. The objective of this research is to examine the psychological factors that affect the interpersonal conflict between mother and son in relation to the psychoanalytic theoretical concepts brought forth by Sigmund Freud. The Sinhala translation by Siri Ediriweera of Sophocles’ Oedipus, the Sinhala translation by K.C. Liyanage of Shakespeare’s Hamlet, Punaragamanaya by Sunil Wijesiriwardana, the Sinhala translation of Henrick Ibson’s Ghost, the Sinhala translation by Sriyarathna Withana of Anton Chekhov’s’ the Seagull, and Punchi Paligu Rena by Henry Jayasena the Sinhala translation of The Glass Menagerie have been referred as the primary sources. The research question of this study is to illustrate what are the psychological factors that affect interpersonal conflict between Mother and Son.
Keywords: Conflict, Characters, Dramas, Interpersonal conflict, Psychoanalytical theory